Games for actors and non-actors - Boal, Augusto (London Routledge, 2004)
Games for Actors and Non-Actors is the classic and best selling book by the founder of Theatre of the Oppressed, Augusto Boal. It sets out the principles and practice of Boal's revolutionary Method, showing how theatre can be used to transform and liberate everyone – actors and non-actors alike! This thoroughly updated and substantially revised second edition includes: two new essays by Boal on major recent projects in Brazil Boal's description of his work with the Royal Shakespeare Company a revised introduction and translator's preface a collection of photographs taken during Boal's workshops, commissioned for this edition new reflections on Forum Theatre
1 THEATRE OF THE OPPRESSED IN EUROPE 18 Introduction 18 The Godrano experience: my first Forum Theatre in Europe or the ultimate spect-actor/protagonist! 19 Feminism in Godrano 20 The police again 21 The oppressed and the oppressors 23 2 THE STRUCTURE OF THE ACTOR’S WORK 29 The primacy of emotion 29 Muscular exercises 31 Sensory exercises 31 Memory exercises 32 vii Imagination exercises 32 Emotion exercises 32 Rationalising emotion 35 A la recherche du temps perdu 37 The dialectical structure of the actor’s interpretation of a role 40 The will 40 The counter-will 43 The dominant will 45 Quantitative variation and qualitative variation 46 3 THE ARSENAL OF THEATRE OF THE OPPRESSED 48 Introduction: a new system of exercises and games from Theatre of the Oppressed 48 Two unities 49 Five categories of game and exercise 49 I FEELING WHAT WE TOUCH (RESTRUCTURING MUSCULAR RELATIONS) 50 First series: general exercises 50 1 The cross and the circle 50 2 Colombian hypnosis 51 3 Minimum surface contact 56 4 Pushing against each other 58 5 Joe Egg (aka trust circle) 62 6 The circle of knots 62 7 The actor as ‘subject’: the Greek exercise 64 8 The actor as ‘object’ 66 9 Lifting someone out of a chair 67 10 Equilibrium of the body with an object 67 11 A balloon as an extension of the body 68 12 Racing on chairs 68 13 Rhythm with chairs 68 14 Musical chairs 69 15 Movement with over-premeditation 69 16 Difficulties 69 17 Divide up the movement 70 18 Dissociate coordinated movements 70 CONTENTS viii Second series: walks 70 1 Slow motion 71 2 At a right angle 72 3 Crab 72 4 Crossed legs (aka three-legged race) 72 5 Monkey 73 6 All fours 73 7 Camel walk 73 8 Elephant walk 73 9 Kangaroo walk 73 10 Leaning-against-each-other walk 73 11 Strapped-feet walk 74 12 Wheelbarrow 74 13 As you like it 74 14 Imitating others 74 Third series: massages 74 1 In a circle 75 2 The movement comes back 75 3 Sea waves 75 4 The rolling carpet 76 5 Back massage 77 6 The demon 77 Fourth series: integration games 77 1 Person to person, Quebec-style 77 2 The bear of Poitiers 78 3 The chair 78 4 Leapfrog 79 5 The Brueghel game 79 6 Stick in the mud 80 7 Grandmother’s footsteps 80 8 Millipede 80 9 Apple dance 81 10 Sticky paper 81 11 The wooden sword of Paris 81 12 American football (aka British bulldog) 82 13 Three Irish duels 82 14 Little packets 83 15 Cat and mouse 83 CONTENTS i x 16 Homage to Tex Avery – cat and dog(s) 84 17 The handkerchief game (aka the hat game, aka dog and bone) 84 18 Good day 85 19 Cadavre exquis (aka consequences) 85 20 The parachute 86 21 Balance with an object 86 Fifth series: gravity 86 1 Horizontality sequence 87 2 Verticality sequence 88 3 Sequence of rectilinear and circular movements 89 II LISTENING TO WHAT WE HEAR 92 First series: rhythm 92 1 A round of rhythm and movement 92 2 Game of rhythm and movement 93 3 Changing rhythms 93 4 The machine of rhythms 94 5 The Peruvian ball game 96 6 The clapping series 97 7 West Side Story 98 8 The Portuguese rhythmic shoes 99 9 The two brooms 100 10 The four brooms 101 11 Horseshoe rhythms 101 12 Circular rhythms 101 13 The big chief 101 14 The orchestra and the conductor 101 15 Rhythm dialogue in teams 102 16 Chain rhythm dialogue 102 17 Pretend Brazilian ‘Indians’ 102 18 Lines of five 104 19 The president’s bodyguards 104 20 Walk, stop, justify 104 21 Carnival in Rio 104 22 Bolivian mimosas 105 23 How many ‘A’s in a single ‘A’? 106 24 Two by three by Bradford 106 CONTENTS x 25 Crossing the room 107 26 Circle of names of Belo Horizonte 107 27 Circle of rhythms of Toronto 107 Second series: melody 108 1 Orchestra 108 2 Music and dance 108 Third series: sounds and noises 108 1 Sound and movement 108 2 Ritual sound 109 Fourth series: the rhythm of respiration 109 1 Lying on your back completely relaxed 110 2 Leaning against a wall 110 3 Standing up straight 110 4 Breathe in slowly 110 5 Explosion 110 6 Breathe in slowly while lifting the arms 111 7 The pressure cooker 111 8 Breathe in as quickly as possible 111 9 Breathe in as slowly as possible 111 10 Breathe in deeply through the mouth 111 11 Breathe in with clear definition and lots of energy 111 12 Two groups 112 13 Breathe out, standing in a circle 112 14 One actor pretends to pull the stopper out of another’s body 112 15 A, E, I, O, U 113 16 All the actors, standing facing the wall 113 17 Two groups of actors, facing each other 113 18 With their bodies in maximum possible contact with the floor 113 19 Lying on their backs on tables 114 Fifth series: internal rhythms 114 1 Rhythmic images 114 III DYNAMISING SEVERAL SENSES 114 The blind series 115 1 The point of focus, the embrace and the handshake 115 2 Noises 116 CONTENTS x i 3 The imaginary journey 117 4 The glass cobra 118 5 One blind line, one sighted line 118 6 The magnet – positive and negative 119 7 Swedish multiple sculpture 120 8 The vampire of Strasbourg 120 9 The blind car 121 10 What is the object? 121 11 The smell of hands 122 12 The figure-of-eight chicane 122 13 G
Translation of: Jeux pour acteurs et non-acteurs
Keywords: Acting; Games